Expert System of Maize: A User Friendly Device - Yadav, V.K.; Marwaha, Sudeep; Singh, K.P.; Singode, Avinash; Jat, S.L.; Das, Abhijit Kumar (Indian Journal of Extension Education, 2012)
In the era of globalization coupled with electronic information system, traditional extension approaches have not been  able to fulfil the ever increasing expectations of farming communities due to time and money constraints. It seems  computer-based information system may meet the socio-economic and information need of farming community. Expert  system on maize (Zea mays L.) attempts to capture the knowledge of human experts and make it available through  computer programme. It solves problems that are difficult or beyond the capacity of human experts. It provides a list of  varieties and its characteristics, fact sheets about production technology, protection from major insect-pests, diseases,  weeds, nutrient deficiency, value-addition, etc. Maize expert system has four essential components, i.e. the knowledge  acquisition module, the knowledge base, the inference engine and the explanatory interface. The knowledge acquisition  module consists of gathering of knowledge from the panel of experts of different field of maize. It also stores the facts from  textbooks, technical /extension /research bulletins. All these information helps in the creation of knowledge base which  establishes 'antecedent consequent' form of rule. A knowledge engineer further processes it through programming and  refinements. The inference engine is the heart of an expert system. It processes the input i.e. the problem statement. It  matches the problem with attributes stored in its memory tree structure. The explanatory interface allows the user to get  the results in Hypertext markup language, Java script and Cascaded style sheets. This system also explains the procedures  to be followed by famers/ extension workers/ experts to get answer of queries related to maize. Hence it is very useful tool  for dissemination/ accessing relevant information related to maize across the globe.
Keywords: Maize; problem; information